Design and Fabrication of Photo-Responsive Hydrogel for the Application of Functional Contact Lens - Lin, Xiaoxia; Zhang, Haitao; Qin, Yuqing; Hu, Xiaohong (Frontiers in Materials, 2021)
Traditional hydrogel usually had restricted application in biomedical field due to lack of control unit. Azobenzene (AZO) was a typical kind of photo-response molecules, but AZO and its small molecular derivatives had serious problems of uncontrollable recovery and light fatigue. While time and space dependence of polymer motion could solve the problem according to previous research. Herein, it was introduced into hydrogel by polymerization to provide a control unit for hydrogel. Firstly, two kinds of crosslinkable AZO molecules with different functionality, namely AZO crosslinker and AZO monomer, were synthesized to be polymerized with traditional hydrophilic monomers. Thus, two kinds of yellow transparent hydrogels, AZO copolymerized hydrogel and AZO crosslinked hydrogel, were obtained. As important properties for traditional hydrogel contact lenses, gelation time and swelling ratio of hydrogels as a function of AZO concentration as well as crosslinking type were investigated. Moreover, synthesized hydrogels exhibited typical porous morphology, but their size and homogeneity were dependent on the type of hydrogel. As a control unit, reversible and controllable photo-responsive performance was desired for photo-response material. Therefore, detailed photo induced isomerization of both AZO copolymerized hydrogel and crosslinked hydrogel were tracked by UV spectra. The results confirmed the reversible, stable and controllable photo responsive process. In vitro evaluation was used to investigate drug release behavior using orfloxacin and puerarin as model drugs. It was found that AZO addition as well as hydrogel type would influence puerarin release, but would have little effect on the orfloxacin release behavior in hydrogels. Furthermore, isomer type in hydrogel would have some effects on drug release behavior including orfloxacin and puerarin.